Quantitative modelling of fine-scale variations in the Arabidopsis thaliana crossover landscape. (15th February 2022) - Hsu, Yu-Ming; Falque, Matthieu; Martin, Olivier C.
Abstract: Abstract: In, essentially, all species where meiotic crossovers (COs) have been studied, they occur preferentially in open chromatin, typically near gene promoters and to a lesser extent, at the end of genes. Here, in the case of Arabidopsis thaliana, we unveil further trends arising when one considers contextual information, namely summarised epigenetic status, gene or intergenic region size, and degree of divergence between homologs. For instance, we find that intergenic recombination rate is reduced if those regions are less than 1.5 kb in size. Furthermore, we propose that the presence of single nucleotide polymorphisms enhances the rate of CO formation compared to when homologous sequences are identical, in agreement with previous works comparing rates in adjacent homozygous and heterozygous blocks. Lastly, by integrating these different effects, we produce a quantitative and predictive model of the recombination landscape that reproduces much of the experimental variation.